MORPHOLOGICAL AND STRUCTURAL INVESTIGATION OF THE POLY(VINYL CHLORIDE) / GRAPHENE OXIDE COMPOSITES - STÎNGESCU, Luiza; CADAR, Călin; COTEȚ, Liviu Cosmin; BAIA, Lucian; SASZET, Kata; MAGYARI, Klara; MIHIS, Alin Grig; FORȚ (LADIU), Carmen Ioana; STROE, Malvina; MATEI, Elena; NILA, Andreea; ANGHEL, Ion; et al. (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The morphological and structural properties of the poly(vinyl chloride)/graphene oxide (PVC/GO) composites are reported. By the mixture of the two constituents, the PVC/GO composite membranes with a concentration of the GO sheets varying from 0 wt.% to 0.5, 1, 2, 3, 4 and 5 wt.% were prepared. Using scanning electron microscopy (SEM) and the analysis of the atomic force microscopy (AFM) images we observed that as increasing the GO concentration in the PVC mass from 0 wt.% to 5 wt.%, the average surface roughness decreases from 235 µm to 227 µm. Using Raman scattering, we report that as increasing the GO concentration in the PVC mass, the ratio between the relative intensities of the Raman [1]lines situated in the spectral ranges 600-650 and 2850-3000 cm-1 (I600-650/I2850-3000) increases as a consequence of the change of GO carbon atoms hybridization from sp2 to sp3. An increase in the number of C-C bonds, simultaneous with the appearance of O-C=O bonds and the decrease of the chlorine concentration, when the GO concentration increases in the PVC weight is reported by X-ray photoelectron spectroscopy (XPS). The down-shift of the main diffraction signal from 24º to 26º when the GO concentration increases in the PVC/GO composite mass from 0 wt.% to 5 wt.%, confirms the incorporation of GO in the polymeric matrix and the modification of the original PVC sample structure. Using transmission electron microscopy (TEM), no agglomerations of the GO structures within the PVC/GO matrix contrast limit were observed.